DIURNAL VARIATIONS OF PHOTOSYNTHETIC RATES AND XYLEM PRESSURE POTENTIALS IN FOUR DWARF SHRUBS (ERICACEAE) IN AN ALPINE ZONE (15th Symposium on Polar Biology) - ナカノ, タカシ; イシダ, アツシ; NAKANO, Takashi; ISHIDA, Atsushi (National Institute of Polar Research, 1994)
P(論文) Microenvironments, net photosynthetic rates and xylem pressure potentials (XPP) were measured for four evergreen dwarf shrubs (Ericaceae) co-existing under the edge of a Pinus pumila canopy in the alpine region of Mt. Norikura on August 13, 1991. The day was clear till about 12 p.m., frequent fog set in the afternoon. When the leaves were directly exposed to sunlight, their temperature and leaf-to-air vapor pressure deficit (VPD) increased to about 40℃ and 0.06 Pa Pa^<-1>, respectively. Leaf temperature and VPD were less in the afternoon when there was fog. The diurnal changes of net photosynthetic rate showed two peaks in early morning and afternoon, when leaf temperature and VPD were low. Gaultheria pyroloides, Phyllodoce aleutica and Vaccinium vitis-idaea took on greater amounts of carbon during the morning than the afternoon, while the reverse was noted for Rhododendron aureum. V. vitis-idaea had less carbon gain per unit leaf area during the daytime. The carbon gain per dry mass of aerial productive-parts (sum of leaf and stem) did not differ among species, since V. vitis-idaea had a large leaf area ratio. Minimum XPP during the daytime in P. aleutica and V. vitis-idaea was lower than in the other two species. V. vitis-idaea especially showed osmotic adjustment and had ridged cell walls. This species did not, thus, have lower diurnal turgor potential or lower relative water content (RWC) compared with the other species. R. aureum and G. pyroloides with high XPP during daytime did not show osmotic adjustment, and had elastic cell walls. departmental bulletin paper